Analysis of the sustainability of the public debt in light of the volatile oil revenues in Iraq for the period (2005-2015) - اسماعيل, ميثم العيبي; جمعة, احمد حامد (Journal of Economics and Administrative Sciences, 2019)
AbstractThis study deals with the fluctuations of oil revenues and its effect on the public debt. This can be studied through the indicators of debt sustainability, the financial, and economic indicators which express the risk of debt. The study focuses on clarification of the public debt path and its management both domestic and foreign. The sustainability of debt takes an important role according the macroeconomic variables. This study stresses the relationship between the rental economy in Iraq and the risk of the public debt, it is very important to work high oil prices, and on investigating during high work to establish a fund to support the budget deficit. This will reduce future risks arising from the use of public debt to reduce the budget deficit. Thus, the size of the sustainable debt will be maintained.